PENGEMBANGAN MATERI BAHAN AJAR PADA MATA KULIAH WAWASAN KEBANGSAAN BERBASIS KARAKTER PANCASILA - Andi Usman (JURNAL PENDIDIKAN DASAR, 2017)
Abstract: This research is a study on the development of material in the subjectof National Insight based on the character of Pancasila which is referred fromthe National Higher Education Standard (SNPT) and the Indonesian NationalQualification Framework (KKNI). The data were collected from students ofPG-PAUD Study Program, Lecturers of Education Faculty of FKIP Untan,and PG-PAUG Teachers who attended Strata One (S1) in PG-PAUD studyprogram at FKIP Untan. The study material was analyzed based on theinstrument which were filled by 42 respondents, and the result is as follows;(1) On the aspect of Pancasila Philosophy, the respondent's statement (itemscore according to 120) is in scientific study. (2) In the sociology aspect ofrespondent's statement (item score according to 128) in reviewing theapplication of the 1945 Constitution. (3) On the psychological aspect ofrespondent's statement (item score is very suitable 80 and 100) in studyingnational culture of Bhinneka Tunggal Ika. (4) In the aspect of Pancasilacharacter behaviour respondents statements (item score 94 is very suitable andsuitable 89), in reviewing to maintain the integrity of NKRI. (5) Then to thelecturer of the respondent's statement about the teaching materials given in thelearning (item score is suitable 109). The suitability of lecturers who teach thesubjects of National Insight in teaching in PG-PAUD. Then, the researcheralong with the lecturers in the research seminar jointly formulate thesuitability of the material that is based on Pancasila character. For materialharmoniousness developed according to the learning achievement based onKKNI or the Indonesian National Qualification Framework and SNPT orNational Standards of Higher Education. Then as a whole will be produced aLearning Curriculum which is part of curriculum of National Insight subjecton PG-PAUD study program.Keywords: SNPT, KKNI, National Insight, Pancasila Character, learningachievement in PG-PAUD.Abstrak:Penelitian ini merupakan kajian mengenai pengembangan Materibahan ajar pada mata kuliah Wawasan Kebangsaan berbasis karakter Pancasilayang dirujuk dari Standar Nasional Pendidikan Tinggi (SNPT) dan KerangkaKualifikasi Nasional Indonesia (KKNI). Data dikumpulkan dari mahasiswaProdi PG-PAUD, Dosen Ilmu Pendidikan FKIP Untan, serta Guru PG-PAUGyang mengikuti Strata Satu ( S1) pada Prodi PG-PAUD FKIP Untan. Bahankajian dianalisis berdasarkan instrument yang diisi responden dari 42 orang,hasilnya sebagai berikut; (1) Pada aspek Filsafat Pancasila pernyataan responden (item skor sesuai 120) dalam mengkaji secara ilmiah. (2) Padaaspek sosiologi pernyataan responden (item skor sesuai 128) dalam mengkajipenerapan UUD 1945. (3) Pada aspek psikologis pernyataan responden (itemskor sangat sesuai 80 dan sesuai 100) dalam mengkaji budaya nasionalBhinneka Tunggal Ika. (4) Pada aspek pengetahuan berprilaku karakterpancasila pernyataka responden (item skor 94 sangat sesuai dan sesuai 89),dalam mengkaji untuk menjaga keutuhan NKRI. (5) Kemudian kepada dosenpengajar pernyataan responden tentang materi ajar yang diberikan dalampembelajaran (item skor sesuai 109). Kesuaian dosen yang mengampu matakuliah Wawasan Kebangsaan dalam mengajar di PG-PAUD.Kemudian,peneliti bersama teman dosen dalam seminar hasil penelitian secara bersamasama merumuskan kesesuaian materi yang berbaisis karakter Pancasila. Untukkesuaian materi yang dikembangkan sesuai dari capaian pembelajaranberdasarkan KKNI atau Kerangka Kwalifikasi Nasional Indonesia dan SNPTatau Standar Nasional Pendidikan Tinggi. Kemudian secara keseluruhan akandihasilkan Kurikulum Pembelajaran yang merupakan bagian dari kurikulummata kuliah Wawasan Kebangsaan pada program studi PG_PAUD .Kata kunci: SNPT, KKNI, Wawasan Kebangsaan, Karakter Pancasila,capaian pembelajaran pada PG-PAUD.